2011
DOI: 10.1016/s1995-7645(11)60173-9
|View full text |Cite
|
Sign up to set email alerts
|

Floral extract of Tecoma stans: A potent inhibitor of gentamicin-induced nephrotoxicity in vivo

Abstract: The present study indicates a very important role of reactive oxygen species (ROS) and the relation to renal dysfunction and point to the therapeutic potential of Tecoma stans in gentamicin induced nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Gentamicin is a well-known potent, broad spectrum aminoglycoside antibiotic with a low cost and high effectiveness when used against Gram-negative infections (Banday et al, 2008;Salem et al, 2010). However, gentamicin use has been restricted and gentamicin is used carefully owing to its effect of causing nephrotoxicity and hepatotoxicity (Stojiljkovic and Stoiljkovic, 2006;Raju et al, 2011;Nayma et al, 2012;Masakazu et al, 2014). The present study has shown the effects of HPE and how it develops gentamicin-induced nephrotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentamicin is a well-known potent, broad spectrum aminoglycoside antibiotic with a low cost and high effectiveness when used against Gram-negative infections (Banday et al, 2008;Salem et al, 2010). However, gentamicin use has been restricted and gentamicin is used carefully owing to its effect of causing nephrotoxicity and hepatotoxicity (Stojiljkovic and Stoiljkovic, 2006;Raju et al, 2011;Nayma et al, 2012;Masakazu et al, 2014). The present study has shown the effects of HPE and how it develops gentamicin-induced nephrotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that the renal toxicity of gentamicin is due to its selective accumulation in the renal proximal convoluted tubules and its long-term stay, which subsequently leads to the loss of brush border integrity, severe degeneration (vacuolar or hydrophic degeneration) and necrosis in epithelial cells of the proximal tubules, and mononuclear cells have infiltrated in intertubular areas (Raju et al, 2011;Liu et al, 2016;Veljković et al, 2016). In this study, gentamicin-administered group (Group IV) showed congestion and dilatation in the renal blood vessels and severe degeneration (vacuolar or hydrophic degeneration) and necrosis in epithelial cells of the proximal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were weighed once a week and drug dosage was adjusted based on body weight changes. In each group, one third of the rats were sacrificed via exsanguination following anesthesia with chloral hydrate (350 mg/kg) after 20 days of administration (n=10), one third after 40 days of administration (n=10) and one third after 20 days of convalescence (n=10) ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of nephroprotective activity [7,8] Rats were randomly assigned into 4 groups of each 6 animals each. Group-I was kept as normal control receiving saline (0.5 mL, i.p.)…”
Section: Experimental Animals and Proceduresmentioning
confidence: 99%